Phenomenology of Bourdieu’s Theory of Practice: The Relationship Between the Budgeting Process and Culture - Erma Setiawati; Rina Trisnawati, Ph.D; Siti Nurhayati Ning Rahayu (Riset Akuntansi dan Keuangan Indonesia, 2024)
This research scrutinizes the phenomenology of Bourdieu’s Theory of Practice: the relationship between the budgeting process and culture. The research aims to provide an overview of the phenomenon of budget preparation, understand the implementation of performance-based budgeting, and determine the role of Bourdieu’s Theory of Practice in budget preparation and culture. This research used Bourdieu’s Theory of Practice, consisting of Habitus, Capital, and Field. Bourdieu’s Theory of Practice was employed to analyze the phenomenon of budgeting in a social and cultural context. This research is qualitative. The setting of this research was UIN Salatiga. Triangulation techniques were utilized in this research. The research results demonstrated that the budget preparation process at UIN Salatiga started from the Planning Subdivision, which coordinates budget preparation at UIN Salatiga. The budget preparation process was based on the established Strategic Plan and Performance Agreement (Perkin). Fundamentally, budgeting at UIN Salatiga has implemented Performance-Based Budgeting, where each budget prepared must have clear input, output, and outcomes. In this case, Bourdieu’s Theory of Practice plays a role in the preparation, arrangement, implementation, reporting, and evaluation processes. Habitus, Capital, and Arena are highly influential in preparing the budget. Habitus, which Capital strengthens, becomes an essential part of the Arena and the budget preparation process so that a budget is created, which is used as a guideline for activities at UIN Salatiga.